Single Buccal Injection for Anesthesia of Upper First Molar - Rayan S. Hamid; Wafaa K. Fathi; Mohamed S. Suleiman (Al-Rafidain Dental Journal, 2008)
Aims: A clinical trial was carried out to assess the efficiency of a single buccal injection to achieveanesthesia of the buccal aspect of the upper first molar instead of the traditional two injections. Materialsand Methods: The subjects included in the clinical assessment were those needing extraction ofan upper first molar of either side. For the purpose of comparison, the sample was randomly dividedinto two main groups: Group I (control group) which included 100 subjects who were to receive twobuccal injections and a single palatal injection before extraction. While Group II (trial group) included100 subjects who were to receive a single buccal injection and a single palatal injection before extraction.The following data were recorded: Pain on needle insertion, pain on deposition of solution, onsetof surgical anesthesia and adequate surgical anesthesia. Results: The first criterion recorded was painon needle insertion where the results showed no significant difference between both groups. Thesecond criterion was pain on deposition of solution. Here the results also showed no significant differencebetween both groups in this aspect. For onset of surgical anesthesia, no significant difference wasshown between both groups. In regard to pain grade experienced during surgery for both groups, theresults showed that grade A anesthesia was recorded in 95% of patients in group I , whereas in 93% ofpatients in group II. Grade B anesthesia was recorded in 5% of patients in group I and in 7% of patientsin group II. Statistically speaking, no significant difference was disclosed in regard to pain assessedduring the extraction of the tooth between both groups. Conclusions: The achievement of successfullocal anesthesia is a continual challenge in dentistry. Any suggested new approach for achieving adequateanesthesia for either the maxilla or mandible as long as it is safe and effective can be recommendedfor routine dental care.